Evaluation of three methods for use of bovine serum albumin in bull spermatozoa sexing - Gonzales Aparicio, Gonzalo W. (2016)
This study was conducted to determine the possibility to vary the proportion of bull spermatozoa with Y chromosome by using bovine serum albumin (BSA) in three methods: Double centrifugation in BSA (M1); centrifugation and migration in BSA (M2); Double migration in BSA (M3). The sperm samples were stored for 20-24 hours at 5 °C and then frozen in liquid nitrogen. The variation in the proportion of spermatozoa with Y chromosome (f-body) was determined by staining with quinacrine dihydrochloride. No significant difference was observed in the percentage of f-body (48.4±5.9% for the control and from 45.8±5.5 to 47.2±4.9% for the treatments. The spermatozoa retrieval rate was 50.7% for M1, 36.2% for M2, and 21.4% for M3 (p<0.01). The effect of ASB on sperm characteristics was significant (p<0.01): the sperm vitality was reduced from 64.2% in the control to 42.5, 37.2 and 27.2% in M1, M2 and M3 respectively; motility was reduced from 83.1% in the control to 48.1, 31.9 and 23.1% in M1, M2 and M3 respectively; the percentage of sperm with functional membrane was reduced from 64.6% in the control to 42.7, 42.6 and 39.6% in M1, M2 and M3 respectively; and the percentage of live sperm with unreacted acrosome was 58.1% in the control and 35.1, 30.2 and 20.5% in M1, M2 and M3 respectively. Sperm characteristics of frozen semen were highly affected (p<0.01) making them unviable.